Frankfurtska ali švedska kuhinja? - Ledinek Lozej, Špela (Etnolog. Nova vrsta (Ljubljana), 2016)
The article outlines the history of the discourses about the architecture, design and household management aspects of the kitchen, with emphasis on the design concept of the Frankfurt and Swedish kitchens. This is followed by a presentation of the echoes in the discourses about the architecture, design and household management aspects of the kitchen in Slovenia, and the appropriation of such concepts in concrete dwelling practices.
Keywords: stanovanjska kultura; kuhinje; kuhinjsko pohištvo; kuhinjska oprema; architecture; arhitektura; oblikovanje; Goriška; Slovenia; Slovenija; zgodovinski pregledi